2022
DOI: 10.3390/app12178909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Self-Compaction on the Airflow Resistance of Aerated Wheat Bulks (Triticum aestivum L., cv. ‘Pionier’)

Abstract: Aeration is a key post-harvest grain processing operation that forces air through the pore volume of the grain bulk to establish favorable conditions to maintain grain quality and improve its storability. However, during storage, grain bulk experiences self-compaction due to its dead weight, which alters the bulk properties and impedes the uniform flow of air during aeration. Thus, this study focused on investigating the effect of self-compaction on the pressure drop ΔP of wheat bulk (Triticum aestivum L., cv.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…They observed that the pressure drop or air flow resistance increased up to 24.76% for storage period of 236 h at the bulk depth of 3.40 m and air velocity of 0.10 ms −1 . 40 Therefore, self-compaction should be considered while designing aerated storage systems. A smart aeration control system can also be effectively used in the storage system.…”
Section: ■ Storage Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the pressure drop or air flow resistance increased up to 24.76% for storage period of 236 h at the bulk depth of 3.40 m and air velocity of 0.10 ms −1 . 40 Therefore, self-compaction should be considered while designing aerated storage systems. A smart aeration control system can also be effectively used in the storage system.…”
Section: ■ Storage Facilitymentioning
confidence: 99%
“…Ramaj et al studied the effect of self-compaction on the resistance to air flow of wheat bulk. They observed that the pressure drop or air flow resistance increased up to 24.76% for storage period of 236 h at the bulk depth of 3.40 m and air velocity of 0.10 ms –1 . Therefore, self-compaction should be considered while designing aerated storage systems.…”
Section: Storage Facilitymentioning
confidence: 99%
“…The non-uniform porosity distribution formula of wheat grain piles in silos in this study is as follows [19], with the variation range of non-uniform porosity with a depth of 0.37-0.42 being obtained via Equation (10), and the average value of 0.40 being taken as the uniform porosity:…”
Section: Mesh Model and Parameter Settingsmentioning
confidence: 99%
“…However, the heat and moisture transfer inside the grain pile during the drying process is complex [18]. For this reason, many drying models have been used to study the drying process for wheat grain piles [19]. There are more than 100 different thin-layer drying models based on semi-theoretical models and the empirical models used in grain piles under different drying conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the resource use of deep learning models for weed detection in smart agriculture [5] and the impact of microbial preparations on yields and soil nutrients [6] are discussed. In addition, it examines the energy consumption and environmental impact of lettuce production [7] and the resistance to airflow in aerated wheat masses [8]. Finally, it investigates real-time plant classification using deep learning techniques [9] and the design of a controller for pH regulation of liquid fertilizers [10].…”
Section: Contemporary Systems For Intelligent Farmingmentioning
confidence: 99%